Assessment of genetic diversity and population structure of groundnut cultivars using morphological characters: Assessment of genetic diversity and population structure of groundnut cultivars using morphological characters - M UMADEVI; T KALAIMAGAL; R SASIKALA; P SHANTHI (Journal of Oilseeds Research, 2023)
Forty six germplasm of groundnut (Arachis hypogaea L.) evaluated under kharif season have been classified using Principal component analysis (PCA) based on correlation matrix yielding eigen values and eigen vectors. Multivariate analysis of phenotypic characters extracted eight principal components (PC) using the mean performance of the genotypes and showed that the first three principal components contributed 61.75% of observed variability amongst the 46 genotypes with the eigen value >1 and PC1 accounted for 25.60% of the total morphological variation for the traits. The information given in this paper will be valuable in the efficient management and utilization of the groundnut genetic resources.